Agency equilibrium - Jonathan Newton (Games, 2019)
Agency may be exercised by different entities (e.g., individuals, firms, households). A given individual can form part of multiple agents (e.g., he may belong to a firm and a household). The set of agents that act in a given situation might not be common knowledge. We adapt the standard model of incomplete information to model such situations.
Keywords: 330; agency; equilibrium; individualism; collectivism